Rigid-flexible Coupling Dynamics Simulation of a Servo Motor Planetary Reducer for Robot Joint - Jianqing Zhou; Fuzheng Qu (Jixie chuandong)
The joint motor is one of the core components of the foot robot，and its dynamic response directly affects the performance of the robot. Among them，the planetary reducer is a precision mechanical transmission mechanism，and its transmission accuracy is closely related to the deformation of key parts. Therefore，by using Adams，a rigid-flexible coupling dynamics simulation model of the joint motor is established to simulate the transient output characteristics during the startup process. In the model，the key parts are flexibly processed，and the motion pair constraints between the parts are set. The Hertz contact theory is used to calculate the contact stiffness coefficient of the planetary gear and the sun gear and the inner gear ring. The simulation results show that the dynamic characteristics of the joint motor are closely related to the acceleration time and inertial load. A larger acceleration time and a smaller inertial load are beneficial to improve its dynamic performance.